Necrotizing fasciitis—A catastrophic complication following routine tibia fracture surgery: A case report and literature review. Issue 23 (June 2017) - Shang, Shuai; Zhang, Ruipeng; Hou, Zhiyong
Abstract: Rationale: Necrotizing fasciitis (NF) is defined as a rare, life-threatening, rapidly spreading soft tissue infection resulting from a polymicrobial origin, with a predominance of anaerobic organisms that presents with necrosis of the muscle, fascia, and surrounding soft tissue. Patient concerns and diagnoses: A 64-year-old male who sustained tibia fracture caused by falling from a height underwent a tibia surgery with minimally invasive plate osteosynthesis technique in another institution. Postoperatively, the patient had development of a very uncommon NF at the site of the tibia procedure. When the patient was transferred to our unit, he rapidly processed to toxic shock and coagulopathy. Interventions and outcomes: Although the patient underwent antibiotics treatment in the emergency room and was transferred to the operating room for surgery promptly, the patient's condition deteriorated rapidly and he died of septic shock and multiple organ failure unfortunately. Lessons: Our study aims to highlight the risk of NF in the elderly with diabetes during the perioperative period even if the injury is a simple closed fracture. Physicians must be vigilant to early inflammatory signs and pain in immunosuppressed patients.